Eksplorasi Etnomatematika Kesenian Balo-Balo pada Prosesi Mantu Poci Tegal - Syafa’at, Firman; Khoirotunnisa; Fadhilah, Nurul; Sholikhah, Alimatus (Circle: Jurnal Pendidikan Matematika, 2021)
Mathematics learning is continuously innovating in order to provide new nuances in teaching and learning mathematics activities. Ethnomathematics is one of the innovations in mathematics learning. Ethnomathematics combines mathematical concepts with regional culture. The purpose of this research was to identify the mathematical concept in the art of balo-balo in the culture of the mantu poci Tegal. This research was an explorative research that used interview, observation, documentation, and literature studies methods. The result of this research showed that there are some mathematical concepts in the balo-balo musical instrument which includes a rectangular shape on the saron, a circle on the gong, a tube on the drum. In the balo-balo dance there are the concepts of reflection, translation, rotation, and number sequences. This mathematical concept can be used as a reference for mathematics learning media.